Layanan Sistem Antrian Pasien Dengan Menggunakan Simulasi Monte Carlo Pada Klinik Pratama Bertha - Desi, Efani; Lestari, Silvi; Zikrina (LPPM Universitas Potensi Utama, 2022)
In the process of health care, serving patients who seek treatment is very important. Service must be done very quickly. In order for the service process to be carried out quickly, a simulation is needed in the service queue process. Monte Carlo simulation is a queue simulation that is very suitable to be applied in this service process. Because of this Monte Carlo simulation, the calculation uses mathematical theory to process the completion of each patient service queue. So that the queue service process can be calculated more accurately and minimally from errors. Monte Carlo simulation can also be done manually by using calculations in Ms. Excel and can also be made in the form of an application that is easy to apply. With this monte carlo simulation, information is obtained for the calculation process of each queue in patient care can be done quickly and the errors caused in each calculation process are very minimal. The results of the information that will be obtained from this simulation are the average time for patient service to come to be served, the average time for patient service in the queue system until the patient is finished being served. It can be concluded that this Monte Carlo simulation is suitable to be applied to the Patient Queue System Service System Using Monte Carlo Simulation at the Bertha Primary Clinic.